2008
DOI: 10.1093/intimm/dxm140
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of histone H4 acetylation by transcription factor E2A in Ig gene conversion

Abstract: Recent studies implicate the transcription factor E2A in Ig diversification such as somatic hypermutation or gene conversion (GCV). GCV also requires active Ig transcription, expression of the activation-induced deaminase (AID) and a set of homologous recombination factors. We have disrupted the E2A gene in the chicken B-cell line DT40 and found greatly diminished rate of GCV without changes in the levels of transcripts from AID and Ig heavy chain or Ig light chain (IgL) genes. However, chromatin immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Our study builds on a number of previous studies implicating E boxes in the targeting of SHM (3336). The most recent of these, by Tanaka et al (34), found that the three E boxes in the murine Igκ intronic and 3' enhancers were required to detect SHM reliably in a GFP reversion assay in DT40 cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our study builds on a number of previous studies implicating E boxes in the targeting of SHM (3336). The most recent of these, by Tanaka et al (34), found that the three E boxes in the murine Igκ intronic and 3' enhancers were required to detect SHM reliably in a GFP reversion assay in DT40 cells.…”
Section: Discussionmentioning
confidence: 89%
“…The most obvious E protein candidates are those encoded by E2a , including E47, which has been shown to bind the IgL locus in DT40 cells (37). Disruption of E2a in DT40 cells reduces both SHM and GCV, although there is disagreement concerning the mechanism of this (35, 36). Notably, two-thirds of the E boxes in the DIVAC cores conform to the subtype preferred by E2 a-encoded proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial data support a role for E-box binding factors, including the E2a -encoded proteins E12 and E47 [53]. Disruption of E2a in DT40 cells reduced the frequency of SH/GCV [59],[60] as did overexpression of the E protein inhibitors Id1 and Id3 [61]. E12 and E47 prefer to bind the CASSTG (S = C or G) subtype of E-box [62], and while mutation of this subtype reduces DIVAC function, mutation of E-boxes predicted to be bound poorly by E12/E47 does also [37].…”
Section: Discussionmentioning
confidence: 98%
“…H4K8ac increased concomitantly with V H DJ H mutations in human BL2 cells upon treatment with trichostatin A (TSA), a histone deacetylase (HDAC) inhibitor [45]. Sustained H4K8ac in VλJλ region required E2A, whose inactivation led to decreased mutations [29, 46]. Decreased H3K4me3 in V H DJ H regions in BL2 cells upon knock-down of histone chaperone suppressor of Ty6 (Spt6) correlated with reduction in V H DJ H mutations [18].…”
Section: Epigenetics Of Shm and Csrmentioning
confidence: 99%